The Relationship Between Range of Motion and Injuries in Adolescent Dancers and Sportspersons: A Systematic Review - Storm, Joyce M.; Wolman, Roger; Bakker, Eric W. P.; Wyon, Matthew A. (Frontiers in Psychology, 2018)
Background: The frequent and intensive training and performance of pre-professional ballet dancers and sportspersons is offered at a time when young ballet dancers and young athletes may be vulnerable to injury due to the progress through adolescence and growth spurts. Hypothesis: There are changes in range of motion during the progress through adolescence and growth periods in dancers and sportspersons. These changes in ROM can be linked to the increase of injury. Objectives: The primary aim of this systematic review is to determine whether there are changes in ROM during the progress through adolescence and growth spurts in dancers and sportspersons. The secondary aim is to determine whether these changes can predict the risk of injuries for adolescent dancers and sportspersons. Search Strategy: Pubmed, Cochrane Register of Controlled Trails (CENTRAL), Cochrane Database of Systematic Reviews (CDSR), EBSCO Host databases: CINAHL Plus, MEDLINE, SPORTDiscus, Embase were searched using MeSH terms. Manual search in the Journal of Dance Medicine and Science and screening of the reference lists of identified studies and reviews was conducted. Selection criteria: Studies included adolescent dancers and sportspersons, aged 8-18, both sexes, growth spurt related to changes in ROM and injury incidence. Data collection and analysis: Search strategy was performed in the flow diagram of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Two reviewers independently appraised each included study using Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) for methodological quality of the included studies. For data extraction, the following information was systematically extracted: first author and year of publication, study design, participants (sample size of mean age), age, maturation (if assessed), intervention, outcome(s) and some notes of each study. For evaluation of the risk of bias and precision the Research Triangle Institute Item Bank (RTI-IB) is included. Main results: Seven observational studies met the inclusion criteria of this current review. The results of this review suggest that there are changes in ROM during the progress through adolescence and growth spurts in dancers and sportspersons. These changes may lead to an increase in injury incidence. Conclusion: There is evidence linking to changes in ROM